OptiPrep™ Density Gradient Solutions for Mammalian Organelles - John Graham (The Scientific World Journal)
Any density gradient for the isolation of mammalian organelles should ideally only expose the sedimenting biological particles to an increasing concentration of the gradient solute. Thus they will experience only an increasing density and viscosity, other parameters such as osmolality, pH, ionic strength and the concentration of important additives (such as EDTA and DTT) should remain as close to constant as possible. This Protocol Article describes the strategies for the dilution of OptiPrep™ in order to prepare such solutions for mammalian organelles and membranes.